Coexistence of Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola in the Red Bacterial Complex in Chronic Periodontitis Subjects - Ardila Medina, Carlos Martín; Ariza Garcés, Astrid Adriana; Guzmán Zuluaga, Isabel Cristina (International journal of odontostomatology, 2014)
Previous reports showed that periodontitis is associated with different microorganisms rather than individual periodontopathogens in the dental biofilm. The purpose of the current study was to evaluate the coexistence and relationship among Porphyromonas gingivalis, Tanerella forsythia, and Treponema denticola in the red complex, noting its association with the severity of periodontitis. In this cross sectional study, 96 subjects, aged 33 to 82 years (with 18 residual teeth) with chronic periodontitis who attended the dental clinics of the Universidad de Antioquia in Medellín, Colombia were invited to participate. The presence or absence of bleeding on probing and plaque were registered. Probing depth and clinical attachment level were measured at all approximal, buccal and lingual surfaces. Microbial sampling on periodontitis patients was performed on pockets >5 mm. The presence of P. gingivalis, T. forsythia, and T. denticola was detected by PCR using primers designed to target the respective 16S rRNA gene sequences. The coexistence of the three periodontopathogens was the most frequent (25 subjects). A statistically significant association between the three bacteria was observed (P. gingivalis and T. forsythia, P<0.0001; P. gingivalis and T. denticola, P=0.001; T. forsythia and T. denticola, P<0.0001). Similarly, the logistic regression analysis showed a significant association among periodontopathogens. The most relevant was observed between P. gingivalis and T. forsythia (OR=6.1). In conclusion, the present study found a significant association in the coexistence of P. gingivalis, T. forsythia and T. denticola, and they related strongly to clinical parameters of inflammation and periodontal destruction.